Novel composite Zr/PBI-O-PhT membranes for HT-PEFC applications - Kondratenko, Mikhail S.; Ponomarev, Igor I.; Gallyamov, Marat O.; Razorenov, Dmitry Yu; Volkova, Yulia A.; Kharitonova, Elena P.; Khokhlov, Alexei R. (Beilstein Journal of Nanotechnology, 2013)
Novel composite membranes for high temperature polymer-electrolyte fuel cells (HT-PEFC) based on a poly[oxy-3,3-bis(4′-benzimidazol-2″-ylphenyl)phtalide-5″(6″)-diyl] (PBI-O-PhT) polymer with small amounts of added Zr were prepared. It was shown in a model reaction between zirconium acetylacetonate (Zr(acac)4) and benzimidazole (BI) that Zr-atoms are capable to form chemical bonds with BI. Thus, Zr may be used as a crosslinking agent for PBI membranes. The obtained Zr/PBI-O-PhT composite membranes were examined by means of SAXS, thermomechanical analysis (TMA), and were tested in operating fuel cells by means of stationary voltammetry and impedance spectroscopy. The new membranes showed excellent stability in a 2000-hour fuel cell (FC) durability test. The modification of the PBI-O-PhT films with Zr facilitated an increase of the phosphoric acid (PA) uptake by the membranes, which resulted in an up to 2.5 times increased proton conductivity. The existence of an optimal amount of Zr content in the modified PBI-O-PhT film was shown. Larger amounts of Zr lead to a lower PA doping level and a reduced conductivity due to an excessively high degree of crosslinking.
Keywords: composite; high temperature polymer-electrolyte fuel cells (HT-PEFC); impedance spectroscopy; polybenzimidazole (PBI); zirconium